2011
DOI: 10.1016/j.bmc.2011.01.060
|View full text |Cite
|
Sign up to set email alerts
|

CD22-Antagonists with nanomolar potency: The synergistic effect of hydrophobic groups at C-2 and C-9 of sialic acid scaffold

Abstract: In earlier studies, we identified the C-9 amido derivative 1 (9-(4'-hydroxy-4-biphenyl)acetamido-9-deoxy-Neu5Gcα2-6GalOMP) and the C-9 amino derivative 2 (9-(4'-hydroxy-4-biphenyl)methylamino-9-deoxy-Neu5Gcα2-6GalOMP) have the most promising affinity for mouse CD22 and human CD22, respectively. Replacing the subterminal galactose residue (2-6Gal-OMP) of 1 with benzyl (5) or biphenylmethyl (6) as aglycone led to even higher potency for mCD22. In this study, both compounds showed improved potency and selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
2
29
0
2
Order By: Relevance
“…Surprisingly, 17 a (Entry 26) does not bind to CD22, although the o-nosyl substituent does not prohibit binding of 9 k. As reported by Kiso and colleagues, [19] intramolecular attraction between benzyl at the 2-position and biphenyl at the 9-position can lead to a hydrophobic collapse. The introduction of an onosyl group at the 5-position may further support this process, abolishing the binding of 17 a.…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 64%
See 2 more Smart Citations
“…Surprisingly, 17 a (Entry 26) does not bind to CD22, although the o-nosyl substituent does not prohibit binding of 9 k. As reported by Kiso and colleagues, [19] intramolecular attraction between benzyl at the 2-position and biphenyl at the 9-position can lead to a hydrophobic collapse. The introduction of an onosyl group at the 5-position may further support this process, abolishing the binding of 17 a.…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 64%
“…[16,17] CD22 recognizes sialic acid a2,6-linked to d-Gal, d-GalNAc (!1), or d-GlcNAc. A decrease in the structural complexity yielded sialic acid derivatives 2-4 [15,18,19] ( Figure 1), indicating that a biphenyl carboxamide moiety at the 9-position can improve affinity substantially. When this extension in the 9-position was applied to the disaccharide epitope, ligands such as 5 and 6 exhibiting sub-micromolar affinities were identified.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, several groups have generated ligands of CD22 with 100-1000 fold higher affinity than the natural ligand, but the best of these have not demonstrated adequate selectivity. 36, 38, 39, 41 For example, although we have shown that doxorubicin-loaded liposomes displaying a high affinity ligand of CD22 (Fig. 1, compound 4 ) are effective in prolonging life in a murine model of disseminated human B cell lymphoma, this ligand exhibits a major cross-reactivity with sialoadhesin (Siglec-1, mSn), expressed on macrophages, which mediate rapid clearance of the liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, besides the routine measurement of intracellular calcium as a marker for B-cell activation and cell surface binding to assess the affinity for CD22, the biological significance of CD22-targeting agents, particularly those derived from synthetic sialosides, 40,41,[45][46][47] should be substantiated with a suitable cytotoxicity assay, as exemplified by the capability of liposomal nanoparticles displaying both antigen and CD22L to induce antigen-specific B-cell apoptosis. 5 mg/mL; GAH, 10 mg/mL), and Wet-III (lane 7; hLL2, 7.5 mg/mL; GAH, 10 mg/mL; anti-IgM, 1 mg/mL).…”
Section: Discussionmentioning
confidence: 99%